PERLINDUNGAN KONSUMEN YANG DIRUGIKAN OLEH PELAKU USAHA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Mohd. Yusuf D.M.; Dedy Siswanto; Alam Karta (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This law on consumer protection has indeed been issued but in the process of implementation or application of the law itself it has not been maximized or in other words the existing regulations in the law are not in accordance with reality. In several cases, violations were found which were detrimental to consumers, which of course were related to the responsibility of producers (business actors) at levels that were considered to endanger the health and even the lives of consumers. The condition of consumers who suffer a lot of losses requires increased efforts to protect them, so that their rights can be upheld. But on the other hand, this protection must also protect the existence of producers who are very essential in the country's economy. Therefore, we need legislation that can protect both parties. This consumer protection issue will never run out and will always be the subject of discussion in society. As long as there are still many consumers who are harmed, the problem will never be resolved. Therefore, it is necessary to pay attention to the issue of consumer protection. The formulation of the problem in this study is the protection of consumers who are harmed by business actors based on Law No. 8 of 1999 concerning consumer protection. The method used is normative legal research. Based on the results of the study it is known that consumer protection is harmed by business actors based on Law Number 8 of 1999 concerning consumer protection that consumers are all users of goods and/or services available in society, both for their own interests, family, other people, and other living things and not for trade.